Change of Seasons: Trade Relations in Byzantine Beer Sheva - Benenstein, Nicolas; Varga, Daniel (Antiguo Oriente, 2024)
The last decades of archeological research and excavations in Beer Sheva have uncovered important remains that enable scholars to better understand the development of the city in the Late Roman and Byzantine periods. This article presents the first synthesis of the major ceramic assemblages of imported fine ware that were discovered during excavations in Beer Sheva. The following paper will address three issues: first, it will provide a description and classification of the finds from various excavations in Beer Sheva; second, it will present a quantitative analysis of the ceramic finds; and third, it will clarify the connection between the city of Beer Sheva and the ceramic production centers in an attempt to understand the role that Beer Sheva played in the trade network established in the northern Negev in the Late Roman and Byzantine periods. The ceramic study presented here supports our understanding of the development of Beer Sheva and the evolution of its role in the northern Negev from the 4th century CE as a military and administrative local center, its importance during the 5th and 6th centuries and its abandonment in the Early Islamic period in the first half of the 8th century.